Pengaruh Model Learning Cycle 5E Berbantuan Media Powtoon terhadap HOTS Literasi Siswa pada Materi Laju Reaksi - Filadelfiansi Dawolo; Retno Dwi Suyanti (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
One of the problems in science learning at the high school level is the low scientific literacy skills based on students' Higher Order Thinking Skills (HOTS), especially in the aspects of analysis (C4), evaluation (C5), and creation (C6). This study aims to analyze the improvement of students' HOTS literacy through the application of the 5E Learning Cycle model assisted by Powtoon media on the Reaction Rate material in class XI of SMA Negeri 2 Medan, and to describe the HOTS literacy aspects that are most developed. This study uses a quantitative approach with a pre-experimental design of one-group pretest-posttest type on 36 students. The results showed that the average pre-test score of 34.22 increased to 85.22 in the post-test with an N-gain value of 0.78 (high category). The t-test results showed a statistically significant increase. The percentage of HOTS literacy indicators achieved showed that analysis (C4) achieved 77.27%, evaluation (C5) achieved 74.87%, and creativity (C6) achieved 50%. These findings indicate that implementing the 5E Learning Cycle model with the help of Powtoon has the potential to improve students' HOTS literacy, particularly in analysis and evaluation skills.